Survey of awareness of radiation disasters among firefighters in a Japanese prefecture without nuclear power plants - Yamada, Koji; Yamaguchi, Izumi; Urata, Hideko; Hayashida, Naomi (PLOS ONE, 2020)
Japanese firefighting organisations are essentially run as village, town, or city units. The Great Hanshin Earthquake of 1995 led to the establishment of emergency support teams to ensure rapid action in response to disasters beyond the capacities of local fire departments. The 2011 Great East Japan Earthquake involved both a tsunami and a radiation disaster caused by a nuclear reactor meltdown, underscoring the need for responses in complex disasters. This study aimed to assess Nagasaki Prefecture firefighters' preparedness for, awareness of, and anxiety regarding radiation disaster response with the aim of elucidating the factors affecting individuals' decisions to accept or reject assignment to a radiation disaster response team. A questionnaire survey was carried out with 1,122 firefighters in three firefighting departments in Nagasaki Prefecture, which does not have nuclear power plants. In total, 920 questionnaires were returned, and the 784 that were valid were analysed. Among the participants, 39% replied that they would have no difficulty accepting assignment to a radiation disaster response team; most of them were under 30 years old and unmarried. This group also included significantly higher percentages of participants who were confident about radiation disaster response or, if anxious, believed things would turn out fine, as well as those who replied that they were able to use the necessary equipment. Furthermore, this group had significantly higher percentages of participants who replied that they would definitely participate in seminars and those who replied that their level of preparedness for radiation disasters was sufficient. The willingness to be assigned to a radiation disaster response team was linked to confidence about radiation disaster response and about handling materials and/or equipment. Therefore, it is considered that measures to increase firefighters' confidence regarding response to radiation disasters will be linked to more proactive measures if and when such disasters occur.